INVESTIGATION OF THE ELECTRIC AHARONOV–BOHM EFFECT IN A QUANTUM RING - Ghazaryan, A.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The bound states of the electron in a quantum ring in the presence of different scalar potentials in two regions are considered. It is shown that the difference of scalar potentials lifts the degeneracy connected with the sign of orbital angular momentum. The same system with a magnetic flux threading the ring is also considered. The possibility of observing the oscillations of energy levels connected with the difference of scalar potentials and the intensity of the magnetic field that are similar to those of the bound states of the electron in a quantum ring threaded only by the magnetic flux is shown.